Elimination of tumor hypoxia by eribulin demonstrated by 18F-FMISO hypoxia imaging in human tumor xenograft models - Songji Zhao; Wenwen Yu; Naoyuki Ukon; Chengbo Tan; Ken-ichi Nishijima; Yoichi Shimizu; Kei Higashikawa; Tohru Shiga; Hiroko Yamashita; Nagara Tamaki; Yuji Kuge (EJNMMI Research, 2019)
Abstract Background Eribulin, an inhibitor of microtubule dynamics, shows antitumor potency against a variety of solid cancers through its antivascular activity and remodeling of tumor vasculature. 18F-Fluoromisonidazole (18F-FMISO) is the most widely used PET probe for imaging tumor hypoxia. In this study, we utilized 18F-FMISO to clarify the effects of eribulin on the tumor hypoxic condition in comparison with histological findings. Material and methods Mice bearing a human cancer cell xenograft were intraperitoneally administered a single dose of eribulin (0.3 or 1.0 mg/kg) or saline. Three days after the treatment, mice were injected with 18F-FMISO and pimonidazole (hypoxia marker for immunohistochemistry), and intertumoral 18F-FMISO accumulation levels and histological characteristics were determined. PET/CT was performed pre- and post-treatment with eribulin (0.3 mg/kg, i.p.). Results The 18F-FMISO accumulation levels and percent pimonidazole-positive hypoxic area were significantly lower, whereas the number of microvessels was higher in the tumors treated with eribulin. The PET/CT confirmed that 18F-FMISO distribution in the tumor was decreased after the eribulin treatment. Conclusions Using 18F-FMISO, we demonstrated the elimination of the tumor hypoxic condition by eribulin treatment, concomitantly with the increase in microvessel density. These findings indicate that PET imaging using 18F-FMISO may provide the possibility to detect the early treatment response in clinical patients undergoing eribulin treatment.